Yamagu-Tips, digital scientific drawings of helminths and other microscopic organisms - Víllora-Montero, María; Hernández-Orts, Jesús Servando; Palacios-Abella, José Francisco; Montero, Francisco Esteban (Zootaxa, 2025)
In the last third of the 20th century, descriptions of microscopic organisms, particularly parasites, became gradually more detailed, supplemented with new morphological features. Improvements in light and electron microscopy have facilitated the description of previously unnoticed aspects of external and internal anatomy. Higher resolution allows descriptions to become increasingly detailed, together with photographs and videos providing additional information derived from museum specimens. At the same time, as technology improved, researchers began using “software” instead of traditional ink to create drawings of new species. This study introduces Yamagu-Tips, a new method for developing scientific drawings of microorganisms that can be created using Adobe Illustrator and Adobe Photoshop (Adobe Creative Cloud). This method allows automated drawing of contours, volumes, and transparencies in a realistic manner. Despite the “automation” of these computer-aided drawings, the realism or correct schematization of microscopic organisms still depends on the skills of the authors, including their artistic concerns.